Milho bt e inseticidas no manejo de lepidópteros-praga - Farias, Juliano Ricardo (2010)
The objectives of this study were to evaluate the effects of Bt toxin and seeds treatment with insecticides (imidacloprid + thiodicarb) on initial growth of corn and the control of Spodoptera frugiperda (J. E. Smith) in soil; the effect of Bt corn and insecticides (seed treatment with imidacloprid + thiodicarb and spray application of novaluron and/or methomyl) for the control of S. frugiperda in crop shoots during early and late planting seasons; and the effects of Bt corn and insecticides control of S. frugiperda on the occurrences and damages from Diatraea sp. and Helicoverpa zea (Boddie) pests. Three experiments were conducted under field conditions and natural infestation of pests, in Itaara and Santiago, in Rio Grande do Sul state, Brazil, during the 2008/2009 planting seasons. The initial growth of corn was not affected by the production of Bt toxin (Cry1Ab) and insecticide seed treatment in areas without pest infestation. The toxin (Cry1Ab) present in the Bt corn as well as seeds treatment in non-transformed corn effectively protected the plants to cut-off S. frugiperda. Seeds treatment enables the reduction of damages caused by S. frugiperda in Bt corn (Cry1Ab) to the shoots of crops in early infestations. The Bt corn (Cry1Ab) is effective in controlling S. frugiperda, especially when infestations are low to moderate. When high infestations of S. frugiperda occurred in late planting, insecticide spray on Bt corn (Cry1Ab) resulted to less damages and fewer lavae development comparatively with unsprayed plots. Insecticide treatment of nontransformed corn seeds during early infestations of Diatraea sp. and Bt corn reduced the percentage of stems attacked and injuries. However, insecticides sprayed for the control of S. frugiperda had no effect on the percentage of stems attacked and the injuries caused by Diatraea sp.. Application of insecticides to seeds or spraying for the control of S. frugiperda did not affect the percentage of corn ears attacked and the injuries caused by H. zea, while the Bt corn (Cry1Ab) reduced the percentage of ears attacked by H. zea despite not having much effect in reducing the ear-feeding injuries.